Morbidity and Mortality in Patients With Posterior Circulation Aneurysms Treated With the Pipeline Embolization Device: A Subgroup Analysis of the International Retrospective Study of the Pipeline Embolization Device. Issue 3 (18th September 2017) - Lopes, Demetrius K; Jang, Dong-Kyu; Cekirge, Saruhan; Fiorella, David; Hanel, Ricardo A; Kallmes, David F; Levy, Elad I; Lylyk, Pedro
Abstract: BACKGROUND: The safety of Pipeline TM Embolization Device (PED; Medtronic Inc, Dublin, Ireland) in posterior circulation aneurysms is still controversial. OBJECTIVE: To study complications associated with the treatment of posterior circulation aneurysms by conducting a subgroup analysis from the International Retrospective Study of PED registry. METHODS: Data from 91 consecutive patients with 95 posterior circulation aneurysms at 17 centers between July 2008 to February 2013 were analyzed. The primary endpoint was defined as any complication leading to neurological morbidity or death. The outcome predictors were calculated using Kaplan–Meier and Cox regression methods. RESULTS: The mean aneurysm size was 13.8 mm. Aneurysm types were saccular (36.8%), fusiform (29.5%), dissecting (28.4%), and others (5.3%). The median follow-up was 21.1 mo. Twelve (13.2%) patients encountered a primary endpoint event. In multivariate analysis for the primary endpoint, use of ≥3 PEDs and fusiform shape compared with other shapes had hazard ratios (HRs) of 7.77 (95% confidence interval [CI], 2.48-25.86; P = .0007) and 3.48 (95% CI, 1.06-13.39; P = .0488), respectively. The multivariate HR of aneurysm size for neurological morbidity after PED implantation was 1.11 (95% CI, 1.04-1.18; P = .0015), and HRs of ruptured aneurysm and age for neurological mortality were 8.1 (95% CI, 1.31-41.26; P = .0197) and 1.07 (95% CI, 1.02-1.15; P = .0262), respectively. Basilar artery aneurysm had an HR of 3.54 (95% CI, 1.12-14.18, P = .0529) in the univariate analysis for major outcomes. CONCLUSION: PED implantation may be considered for the treatment of posterior circulation aneurysms, especially of saccular or dissecting type. Our major complications appear to be comparable to those reported previously after clipping and coiling in the literature. Neurointerventionists should consider the shape, size, rupture, and location of complex posterior circulation aneurysms as well as age and PED number before the PED placement.